Mid-IR standoff measurement of ageing-related spectroscopic changes in bitumen in the 6 µm (1700 cm−1) region. Part 2: Instrument development and results - Nicholas M. Davis; Jane Hodgkinson; Stephen Staines; Cormac Browne; Stuart McRobbie; Alex Wright; Ralph P. Tatam (Scientific Reports)
Abstract The development and experimental performance of instrumentation to measure ageing-related spectroscopic changes in bitumen is described. Oxidation of bitumen at the surface increases the number of carbonyl (C=O) bonds, and this can be measured in the 6 μm region (1700 cm−1) of the mid-infrared. Standoff measurements of surface reflectivity were performed using 4 discrete wavelengths, 3 for the carbonyl absorption and the fourth as a spectral reference. The standoff height of 20 cm caused problems resulting from the presence of numerous strong absorption lines of atmospheric water in the optical path, which was solved by use of wavelengths centred within available “water windows” and a pathlength-matched reference channel. The instrument was tested using bitumen samples aged artificially using UV exposure. Results illustrating the instrument’s response to bitumen age, along with tolerance to changes in height and tilt, are shown. Measurements made during preliminary field trials on outdoor asphalt are also demonstrated. Part 1 of this paper describes the scientific challenges involved in designing this instrument.